Potentially prolonged psychological distress from postponed Olympic and Paralympic Games during COVID-19 - Career uncertainty in elite athletes - Håkansson, A.; Moesch, K.; Jönsson, C.; Kenttä, G. (International Journal of Environmental Research and Public Health, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has had a significant impact on the world of sports due to periods of home quarantine, bans against public gatherings, travel restrictions, and a large number of postponed or canceled major sporting events. The literature hitherto is sparse, but early indications display signs of psychological impact on elite athletes due to the pandemic. However, beyond acute effects from lockdown and short-term interrupted athletic seasons, the postponed and still uncertain Olympic and Paralympic Games may represent a major career insecurity to many athletes world-wide, and may lead to severe changes to everyday lives and potentially prolonged psychological distress. Given the long-term perspective of these changes, researchers and stakeholders should address mental health and long-term job insecurity in athletes, including a specific focus on those with small financial margins, such as many female athletes, parasports athletes, athletes in smaller sports, and athletes from developing countries. Implications and the need for research are discussed.